Nutrition Phytochemicals Affecting Platelet Signaling and Responsiveness: Implications for Thrombosis and Hemostasis - Tamer, Funda; Tullemans, Bibian M. E.; Kuijpers, Marijke J. E.; Claushuis, Theodora A.M.; Heemskerk, Johan W. M. (Thrombosis and Haemostasis, 2021)
Cardiovascular disease, in particular due to arterial thrombosis, is a leading cause of mortality and morbidity, with crucial roles of platelets in thrombus formation. For multiple plant-derived phytochemicals found in common dietary components, claims have been made regarding cardiovascular health and antiplatelet activities. Here we present a systematic overview of the published effects of common phytochemicals, applied in vitro or in nutritional intervention studies, on agonist-induced platelet activation properties and platelet signaling pathways. Comparing the phytochemical effects per structural class, we included general phenols: curcuminoids (e.g., curcumin), lignans (honokiol, silybin), phenolic acids (caffeic and chlorogenic acid), derivatives of these (shikimic acid), and stilbenoids (isorhapontigenin, resveratrol). Furthermore, we evaluated the flavonoid polyphenols, including anthocyanidins (delphinidin, malvidin), flavan-3-ols (catechins), flavanones (hesperidin), flavones (apigenin, nobiletin), flavonols (kaempferol, myricetin, quercetin), and isoflavones (daidzein, genistein); and terpenoids including carotenes and limonene; and finally miscellaneous compounds like betalains, indoles, organosulfides (diallyl trisulfide), and phytosterols. We furthermore discuss the implications for selected phytochemicals to interfere in thrombosis and hemostasis, indicating their possible clinical relevance. Lastly, we provide guidance on which compounds are of interest for further platelet-related research.
Keywords: hemostasis; nutrition; platelet; signaling; thrombosis